2023
DOI: 10.1038/s41586-023-05728-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-derived 3-IAA influences chemotherapy efficacy in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is expected to be the second most deadly cancer by 2040, owing to the high incidence of metastatic disease and limited responses to treatment1,2. Less than half of all patients respond to the primary treatment for PDAC, chemotherapy3,4, and genetic alterations alone cannot explain this5. Diet is an environmental factor that can influence the response to therapies, but its role in PDAC is unclear. Here, using shotgun metagenomic sequencing and metabolomic screening, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
110
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(112 citation statements)
references
References 50 publications
2
110
0
Order By: Relevance
“…Mechanistically, 3-IAA can be oxidized to various toxic products such as 3-methylene-2-oxindole by neutrophil-derived myeloperoxidase (MPO), thereby inducing neutrophil necrosis and enhancing the inhibitory effects of FIRINOX on tumor growth. 6 This observation was in line with a recent report that neutropenia (low neutrophil count) caused by chemotherapy was associated with longer survival in metastatic PDAC. 7 On the other hand, 3-IAA and MPO co-treatment significantly increase reactive oxygen species (ROS) accumulation by inhibiting antioxidant enzymes glutathione peroxidases3/7 (GPX3/GPX7) expression, and high ROS levels can act as crucial inducer for chemotherapy-induced program cell death.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Mechanistically, 3-IAA can be oxidized to various toxic products such as 3-methylene-2-oxindole by neutrophil-derived myeloperoxidase (MPO), thereby inducing neutrophil necrosis and enhancing the inhibitory effects of FIRINOX on tumor growth. 6 This observation was in line with a recent report that neutropenia (low neutrophil count) caused by chemotherapy was associated with longer survival in metastatic PDAC. 7 On the other hand, 3-IAA and MPO co-treatment significantly increase reactive oxygen species (ROS) accumulation by inhibiting antioxidant enzymes glutathione peroxidases3/7 (GPX3/GPX7) expression, and high ROS levels can act as crucial inducer for chemotherapy-induced program cell death.…”
supporting
confidence: 90%
“…Notably, autophagy has been reported to be extraordinary eminent in PDAC and considered as a promising target for therapy. In line with it, Tintelnot and his colleagues 6 found that high concentration of ROS can subsequently decrease autophagy in cancer cells, which ultimately mediated the synergistic antitumor effect of 3-IAA and FIRINOX (shown in Fig. 1).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…And most of the pancreatic cancer tissues have been detected with bacteria, the majority of which are Gammaproteobacteria , 141 indicating the underlying mechanisms of poor response to chemotherapy in pancreatic cancer. On the other hand, microbiota‐derived tryptophan metabolite indole‐3‐acetic acid enhanced the chemotherapeutic effects of pancreatic cancer via elevating the accumulation of Reactive Oxygen Species (ROS) and downregulating autophagy in cancer cells 142 . And intratumor Clostridium butyricum and its metabolite butyrate could promote susceptibility to ferroptosis in pancreatic cancer, 143 which is a promising way to enhance therapeutic effects 144 .…”
Section: Interactions Between Intratumor Microbiome and Cancer Therapymentioning
confidence: 99%
“…Targeting tumor‐associated CXCR2 + neutrophils and CCR2 + macrophages was reported to improve chemotherapeutic responses in pancreatic ductal adenocarcinoma 342 . In a nutshell, a series of studies have shown that it is necessary to investigate neutrophil heterogeneity in the context of pancreatic cancer treatment 266–343 . For subsequent investigation, the inductive factors of the emergence of diverse neutrophil subsets may be probed, enabling a brand‐new viewpoint for the treatment of pancreatic cancer.…”
Section: Neutrophil Heterogeneity In Diseasesmentioning
confidence: 99%